Role of surface structure in photoelectron emission from solid Ne: impurities, defect and low-coordinated sites - Dmitriev, Yu.A. (Физика низких температур, 2012)
Electron emission was obtained from a solid Ne sample growing from the gas phase on a low temperature
substrate. The surface of the sample was irradiated by the light of an open-source microwave discharge running
in the gaseous Ne. The irradiation produces electron emission from the sample. A second gas flow of D₂ was,
simultaneously, passed onto the substrate avoiding the discharge zone. Free electrons ejected into a vacuum
chamber during the sample growth were detected by means of the electron cyclotron resonance technique. The
emission shows nonmonotonic dependence on the impurity D₂ concentration. At small concentration, the electron
yield is found to increase significantly at increasing the dopant flow rate, while, at moderate concentrations,
the yield tends to decrease with increasing the flow rate. A tentative explanation of the observed effect is presented
based on the exceptional properties which the neon-hydrogen solid mixture is believed to have.